Transtornos comportamentais de crianças atendidas num serviço público de saúde mental: visão dos pais e dos profissionais - Silva, Raquel Caetano Teixeira da (2012)
Human behavior and child development have been the target of many researches and studies. The amount of children suffering from mental health problems is considered a major cause of childhood disorders. It must be remembered that child mental health and behavior disorders are close attached to the family that is significantly influent in development and behavior of its members and essential to adaptation to various situations across the life span. Therefore, it is important to assess behavioral disorders in childhood as they might affect children s development carrying risks to psychosocial disturbances in adult life. In this study, internalizing and externalizing behavior problems were considered as they are equally harmful to child development. The aim of this study was to describe behavioral disorders present in children attended at a Government Mental Health Service in a country town in São Paulo State according to parents and professional staff. 25 parents/carers and 3 psychologists participated in this study. The Achenbach System of Empirically Based Assessment (ASEBA) was used - Child Behavior Checklist (CBCL/6-18) e o Teacher s Report Form (TRF), as well as the information of clinical evolution of each children. From the 25 assessed children, 60% were boys and 56% of parents were biological mothers. 44% of the children were referred to the Mental Health Service by the school due to indiscipline/aggression (28%), post-traumatic stress (28%), and somatization (24%). In the total, parents/carers identified 88% of children with internalizing behavioral problems and 56% with externalizing problems. On the other hand, psychologists identified 56% of children with internalized behavioral problems and 24% with externalizing problems. There was a 0,36 (p<0,07) correlation between parents and psychologists results and = 8,909 (p<0,003) in the Friedman test, asserting that parents/carers do not agree in their assessments of children s behavioral problems. More research is needed to improve theoretical and practical contributions to children s mental health.